Предмет: Алгебра,
автор: Marisabel10061999
Упростите выражение
Приложения:
Ответы
Автор ответа:
0
................................................
Приложения:
Автор ответа:
0
а скалярное произведение можешь решить? только что добавила...
Автор ответа:
0
Я забыл уже как(
Автор ответа:
0
( ......
Автор ответа:
0
(b+2)/(b-1)(b-1) : (b-2)(b+2)/3(b-1)=
3(b+2)(b-1)/(b-1)(b-1)(b-2)(b+2)=
3/(b-1)(b-2)
3/(b-1)(b-2)-3 /(b-2)=(3-3(b-1))/(b-1)(b-2)=(3-3b+3)/(b-1)(b-2)=(6-3b)/(b-1)(b-2)
3(b+2)(b-1)/(b-1)(b-1)(b-2)(b+2)=
3/(b-1)(b-2)
3/(b-1)(b-2)-3 /(b-2)=(3-3(b-1))/(b-1)(b-2)=(3-3b+3)/(b-1)(b-2)=(6-3b)/(b-1)(b-2)
Приложения:
Похожие вопросы
Предмет: Информатика,
автор: Аноним
Предмет: Алгебра,
автор: Аноним
Предмет: Биология,
автор: aysultan006
Предмет: Математика,
автор: 8905646
Предмет: Информатика,
автор: interesyushiisya